Recent range contractions in the globally threatened Pyrenean desman highlight the importance of stream headwater refugia. (20th June 2018) - Quaglietta, L.; Paupério, J.; Martins, F. M. S.; Alves, P. C.; Beja, P.
Abstract: Freshwater ecosystems are among the most threatened in the world, and downstream reaches of stream networks are often the most affected by multiple anthropogenic stressors. In these circumstances, many species currently restricted to stream headwaters may represent remnants of once larger populations, though this is generally difficult to ascertain due to limited historical data. Here, we document a case of range contraction into headwaters of the globally threatened Pyrenean desman Galemys pyrenaicus, a species endemic to South‐western Europe, from surveys carried out in 1993–96 and 2014–15. Geostatistical logistic mixed models were used to relate the probabilities of desman occurrence and extinction to environmental variables in 74 sites within two watersheds in NE Portugal, while controlling for linear (Euclidean) and hydrologic spatial dependencies. In 1993–96, desmans were recorded at 85.1% of sites, and their presence was positively related to stream order and slope. In 2014–15, desmans were only found at 31.1% of sites, and their presence was positively related to slope steepness and negatively to stream order and maximum temperature of the warmest month. The extinction rate across periods was 63.5%, and the probability of extinction increased with stream order and declined with slope steepness. Maps of predicted distribution and extinction indicated that while the species was widely distributed in the first period, it largely disappeared thereafter from the main rivers and the largest tributaries, persisting mostly in stream headwaters in more mountainous areas. The severe decline found in ours and other studies suggests that the conservation status of the Pyrenean desman may need to be upgraded, and highlights the importance of headwater streams for its conservation. Furthermore, this study supports the view that headwater streams may be increasingly important for biodiversity conservation in modified river systems, favouring the permanence of remnant, albeit fragmented populations. Abstract : The Pyrenean desman Galemys pyrenaicus is a globally threatened, ecologically and phylogenetically unique semiaquatic mammal endemic of South‐western Europe, and one of the less‐studied European mammals. Based on long‐term survey data and state‐of‐the‐art non‐invasive genetics and stream geostatistical mixed models, we documented severe desman range contraction in Northeast Portugal, particularly into headwaters, with a 54% naïve occupancy drop and a 63.5% extinction rate in the last two decades. Our results suggest that the conservation status of the Pyrenean desman should be upgraded, and show the importance of headwater refugia for the desmans, supporting the view that these habitats may be increasingly important for biodiversity conservation under the current scenario of increasingly modified river systems, favouring the permanence of remnant, fragmented populations. Photo Credit : ©Joel Sartore/ National Geographic Photo Ark